Analysis of WSN routing protocols for the application of forest fire prevention. (2017) - Cao, Ning; Zhang, Yuanyuan; Li, Guofu; Fei, Xiujuan; Yu, Hua; Wu, Mei; Cao, Shaohua; Xue, Bin; Yu, Xueru
Forests are precious and indispensable natural resource. Using wireless sensor networks (WSN) to establish forest fire prevention system can effectively reduce loss of human and economy. However, monitoring a very large and complex area such as the entire forest by WSN would entail a large number of sensor nodes, which are hard to be replaced or recharged. Such working conditions and constrains give rise to the necessity to make careful design on network protocol for the WSN. In this paper, we compare and analyse several key parameters for the location-based routing protocols and hierarchical routing protocols. This research will assist the users to design or select the best routing protocols for their applications.